The challenges of border issues, documentation, and infrastructure in intra-African trade - Daniels, Aliya Monique (Department of Commercial Law, 2020)
In 21st century post-colonial Africa, African leaders have visualised, mobilised, and worked towards economic advancement nationally, regionally, and continentally. In the past 60 or more years there has been a concentration on regional integration as to achieve economic growth and increase global competitiveness. More recently, intra-African trade has emerged as an essential component of continental economic advancement. However, there have been many obstacles that have hindered intra-African trade from achieving its potential and functioning in a way that truly benefits the continent. This dissertation will examine the effect that some of those challenges and obstacles (including border issues, documentation, and the lack of essential infrastructure), have had on intra-African trade.